Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T15:44:16+01:00
D) -3a(1/3 - a) = -a+3a²
e) (t-2s-1)*7 = 7t - 14s -7
f) 1/2(2a-4b+1) = a -2b +½
g) m(2m+3) = 2m² + 3m
h) 3p(2r+5p-1) = 6pr + 15p² - 3p
i) xy(2x-3y+5) = 2x²y- 3xy² + 5xy
4 5 4
2010-02-20T15:44:55+01:00
D) -3a(1/3 - a)= -a+3a²
e) (t-2s-1)*7 = 7t-14s-7
f) 1/2(2a-4b+1)= a-2b+1/2
g) m(2m+3)= 2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p
i) xy(2x-3y+5)= 2x²y-3xy²+5xy
3 3 3
2010-02-20T15:45:19+01:00
D) -a+3a²
e)7t-14s-7
f)a-2b+½
g)2m²+3m
h)6pr+15p²-3p
i)2x²y-3xy²+5xy
3 3 3